An analysis of artists' practice in hybrid art and the challenges toward Malaysian art scene - Michael, Valerie; Abd Rahman, Khairul Aidil Azlin; Abdul Shukor, Shureen Faris; Mohd Ali, Noor Azizi (Universiti Putra Malaysia Press, 2018)
Living in today's era, artists’ practice in creating artwork is different from those practiced 20 years ago. With the existence of digital art followed by electronic art in the local art scene, the presentation, style and approach have evolved. Back in 2005 and 2007, some exhibitions brought hybrid art concept into an art exhibition. One of the shows was ‘Hybrid+ism’ which highlighted in various disciplines, media, applying unlimited processes and medium. The purpose of this paper is to study the artists’ practice in the hybrid art based on selected artworks. The artworks are selected based on some criteria ranging from experimental, mixed media, multi-disciplines, integration and technology as well as culture aspects. This paper is discussing the hybrid art practice among artists in the Malaysian art scene and the challenges to creating awareness on hybrid practice among audiences.